121k views
4 votes
Given f(x) = x − 7 and g(x) = x2 Find f(g(4)). f(g(4)) =

2 Answers

5 votes

Explanation:

Given f(x) = x − 7 and g(x) = x2 .

Find g(f(4)).

f(x) = x-7

g(x) = x^2

f(4) = 4-7 = -3

g(f(4)) = (-3)^2

(-3)^2 = 9

g(f(4)) is 9

Find f(g(4)).

f(g(4)) = f(g(4)) = 9

Find g(f(−1)).

g(f(−1)) = 64

Find f(g(−1)).

f(g(−1)) = -6

Composition of the functions is sometimes commutative.

hope this helps!! have an amazing day <3

2021 edg

User Maxim Toyberman
by
5.1k points
6 votes
Answer:

The value of the g(f(4)) is 9

Explanation:

As given the expression in the question be as follow.

f(x) = x-7

g(x) = x^2

Now find g(f(4)).

first find f(4)

f(4) = 4-7

= -3

Thus

g(f(4)) = (-3)^2

As

(-3)^2 = 9

Therefore the value of g(f(4)) is 9



User Aludvigsen
by
5.6k points